Stable 1T-phase MoS2 as an effective electron mediator promoting photocatalytic hydrogen production. Issue 19 (8th May 2018) - Shi, Jian-Wen; Zou, Yajun; Ma, Dandan; Fan, Zhaoyang; Cheng, Linhao; Sun, Diankun; Wang, Zeyan; Niu, Chunming; Wang, Lianzhou
Abstract : Novel MoO3 /1T-MoS2 /g-C3 N4 is developed for the first time, where 1T-MoS2 acts as an electron mediator to construct an all-solid-state Z -scheme photocatalyst. Abstract : Coupling two semiconductors together to construct a Z -scheme type photocatalytic system is an efficient strategy to solve the serious recombination challenge of photogenerated electrons and holes. In this work, we develop a novel composite photocatalyst by sandwiching metallic 1T-phase MoS2 nanosheets between MoO3 and g-C3 N4 (MoO3 /1T-MoS2 /g-C3 N4 ) for the first time. The metallic 1T-phase MoS2 acts as an efficient electron mediator between MoO3 and g-C3 N4 to construct an all-solid-state Z -scheme photocatalytic system, resulting in a highly-efficient spatial charge separation and transfer process. Benefiting from this, the newly developed MoO3 /1T-MoS2 /g-C3 N4 exhibits a drastically enhanced photocatalytic H2 evolution rate of 513.0 μmol h −1 g −1 under visible light irradiation (>420 nm), which is nearly 12 times higher than that of the pure g-C3 N4 (39.5 μmol h −1 g −1 ), and 3.5 times higher than that of MoO3 /g-C3 N4 (145.7 μmol h −1 g −1 ). More importantly, the originally unstable 1T-phase MoS2 becomes very stable in MoO3 /1T-MoS2 /g-C3 N4 because of the sandwich structure where 1T-phase MoS2 is protected by MoO3 and g-C3 N4, which endows the photocatalyst with excellent photostability. It is believed that this study will provide new insights into the design of efficient and stable Z -scheme heterostructures for photocatalytic applications.